Psychology for A2-level. - Cardwell, Mike.; Clark, Liz, 1952-; Meldrum, Claire; Cardwell, Mike. (London : Collins, 2004)
This introductory textbook brings together revised coverage of the AS-level and A2 requirements. The text is in eight sections plus a section on exam preparation, providing comprehensive coverage of compulsory and optional AQA(A) units. There are unit summaries throughout and key terms are also highlighted.
Previous ed.: published as Psychology for A level. 2000.
Includes bibliographical references (p. 694-718) and index.
AS/A2.
Keywords: Psychology; Psychology -- Problems, exercises, etc; Psychology